Penentuan Dosis Efektif Pada Pemeriksaan CT Scan Kepala Anak Dengan Software Indose CT - Elshaday S.B Siregar; Ngurah Sutapa; I Wayan Balik Sudarsana (Kappa Journal, 2019)
CT Scan for head data for children have been processed by using a software name IndoseCT. CT Scan usually use for diagnose part of human body, but CT Scan for head is the most. Data processing was carried out with the IndoseCT software to obtain effective dose values. The highest effective dose value with contrast and non contrast received by 1 until 5 years old patients. Examination with contrast has an effective dose value of 1.29 mSv and for non contrast examination has an effective dose value od 1.16 mSv, meanwhile the lowest effective dose for examination with contrast received by 0 until 1 years old patients with value of 0.94 mSv and for non contrast examination of 0.9 mSv received by 16 until 18 years old patient.